Ex vivo investigations on the potential of optical coherence tomography (OCT) as a diagnostic tool for reproductive medicine in a bovine model. Issue 1 (23rd March 2015) - Trottmann, Matthias; Kölle, Sabine; Leeb, Regina; Doering, Daniel; Reese, Sven; Stief, Christian G.; Dulohery, Kate; Leavy, Myles; Kuznetsova, Julia; Homann, Christian; Sroka, Ronald
Abstract : Routine infertility investigations in the male and female include imaging techniques such as ultrasonography and endoscopy (fertiloscopy). However, these techniques lack the resolution to localize vital sperm or to reveal detailed morphological analysis of the oviduct which is often the cause of infertility in females. Therefore we set out to evaluate the efficiency of optical coherence tomography (OCT) as a diagnostic imaging tool for micron‐scale visualization of the male and female genital tract. Using the bovine as a model, the optical features of the Telesto TM, Ganymede TM (both Thorlabs) and Niris TM (Imalux) OCT imaging systems were compared.Comparative visualization of ex vivo bovine testicular tissue by the Telesto TM microscopic optical coherence tomography system (left) and corresponding H&E staining (right). Abstract : Routine infertility investigations in the male and female include imaging techniques such as ultrasonography and endoscopy (fertiloscopy). However, these techniques lack the resolution to localize vital sperm or to reveal detailed morphological analysis of the oviduct which is often the cause of infertility in females. Here, the efficiency of optical coherence tomography (OCT) as a diagnostic imaging tool for micron‐scale visualization of the male and female genital tract is evaluated.